INSTITUTIONAL EFFICIENCY, ENTREPRENEURSHIP, AND THE PREMISES OF ECONOMIC DEVELOPMENT IN THE EASTERN EUROPEAN COUNTRIES - IGNATOV, Augustin (Studia Universitatis Babeș-Bolyai Oeconomica, 2019)
The development gap between the “Old” and “New” member countries of the European Union is an important problem challenging the efficiency and strength of the European single market. In this regard, a subsequent question arises: which actions in the policy making must be undertaken, by both national and supranational authorities, to stimulate cohesion in the EU and which directions should be followed? The present paper tries to answer this question considering the perspective of the Eastern European nations and their economic development premises analysing the aspects of governmental participation in the economy and the influence of entrepreneurship upon long run competitiveness. The research results explicitly underline that entrepreneurship in the Eastern European nations is a determinative driver of long-term economic competitiveness due to its favourable impact upon the formation of human capital, enhancement of innovation potential and overall intellectual resources of nations. The effects of governmental participation in the economy upon the economic growth premises are heterogeneous including on the formation of physical and intellectual capital. Consequently, it was reached the conclusion that the Eastern European Nations should prioritise entrepreneurship since it is capable of boosting human capital creation and, at the same time, they should improve the institutional quality to minimise the factors undermining the business including corruption and red-tape, etc. In such a way, the Eastern European countries can overcome, in the long run, the development gap with the Western EU states and raise their economic potential. JEL classification: F15; O11; O25; O38; L26;